Metagenomics analyses of microbial dynamics associated with putative flavor development in mash fermentation of sake. (15th June 2022) - Nguyen, Nguyen Thanh Hai; Wang, Wen-Yen; Huang, Wei-Ling; Huang, Chao-Li; Chiang, Tzen-Yuh
Abstract: Sake is a traditional alcoholic beverage in Japan. To examine the impact of co-fermentation on microbial composition, fermentation with and without pineapple was conducted. The dynamics of microbial communities during fermentation were investigated using the metagenomics of 16S rRNA and internal transcribed spacers. In regular (RS) and co-fermented (CS) sakes, the fungal microbiota was dominated by Saccharomyces . Hierarchical clustering and non-metric multidimensional scaling identified two phases of bacterial succession. Compared with the dividing point between phases in RS, the transition in CS was delayed by five days. In both experiments, Leuconostoc dominated the premature stage and was replaced by Erwinia in the maturation stage; the alcohol tolerators of Staphylococcus and Bacillus were persistent. In RS, bacterial succession was characterized by a dramatic decrease in Pseudomonas in the maturation stage, whereas it occurred earlier in the premature stage in CS. Nineteen genera were exclusively found in CS, suggesting that co-fermentation may nurture diverse bacteria that enrich the sake flavor. Analysis of functional pathways by PICRUSt2 revealed that sugar alcohol degradation was fundamental to fermentation, whereas flavor-rich CS was attributable to the activation of l -arginine biosynthesis and amine and polyamine degradation. Aerococcus was positively correlated with enzymes involved in phenylethyl metabolism. Highlights: In sake fermentation, fungal microbiota was dominated by Saccharomyces. Dynamics of bacterial community in sake fermentation is divided into two phases. Leuconostoc dominated premature stage, while replaced by Erwinia in maturing stage. Alcohol tolerators of Staphylococcus and Bacillus were persistent in both sakes. Unique functional pathways from extra bacteria in cofermentation add sake flavors.